THE INFLUENCE OF ORGANIZATIONAL CULTURE ON JOB SATISFACTION - Janićijević, Nebojša; Nikčević, Gordana; Vasić, Vladimir (Economic Annals, 2018)
The paper explains the impact of organizational culture on employees’ job satisfaction. Organizational culture, through its values and norms, shapes an organization’s internal context and thus impacts different elements, including job satisfaction. The paper develops two theoretical explanations of organizational culture’s impact on job satisfaction, which are verified through empirical research on a sample of 324 employees from 16 companies in Montenegro. The first theoretcal explanation starts with the assumption that organizational culture impacts job satisfaction by harmonizing its values and norms with specific types of employee needs, while the second starts with the assumption that organizational culture impacts job satisfaction based on the content of its values and norms, regardless of the employees’ needs. The research shows that employees’ job satisfaction level systematically and significantly varies in different organizational culture types, proving that organizational culture is a job satisfaction factor; and that organizational culture does not impact the job satisfaction level by harmonizing with employee needs but through the content of its values and norms. It also shows that the level of job satisfaction is highest in task culture, followed by power culture, and lowest in role culture.